Resposta adaptativa de células planctônicas e sésseis de Salmonella Enteritidis ao óleo essencial de cravo, eugenol, quaternário de amônio e ácido lático - Coelho, Mariana Silva (2017)
Surfaces and food contamination by deteriorating and pathogenic microorganisms such as Salmonella sp. is a concern in the food industry. Essential oils and their major compounds have demonstrated antimicrobial activity on these microorganisms. They can modify the foods sensorial characteristics to which they are added in order to preserve them. Front of this, these antimicrobials have been used in conjunction with other barriers, in order that it is used in smaller quantities, so they can be found in sublethal concentrations. Thus, the physiological characteristics of these microorganisms may confer resistance to antimicrobial agents, such as, for instance, sanitizers used in hygienic procedures or antimicrobials used in food preservation. This frequent exposure to sublethal concentrations may lead to the appearance of more resistant microorganisms. In this context, the objective of this study was to evaluate the adaptation of planktonic and sessile cells of Salmonella enterica sorovar Enteritidis to the clove essential oil, its majoritarian compound eugenol, quaternary ammonium and acid stress. In order to evaluate the adaptation of the planktonic cells, were firstly analyzed the clove essential oil minimum bactericidal concentrations (MBC) and its major compound eugenol at concentrations of 0.5; 0.9; 1.9; 3.9; 7.8; 15.6; 31.2 and 62.5 mg.mL-1 and the quaternary ammonium at concentrations of 0.1; 0.2; 0.5; 0.9; 1.9 mg.mL-1, which were determined using the broth microdilution in 96-well polystyrene plates and incubated at 37 ° C for 24 hours. To evaluate the adaptation of the sessile cells, were firstly analyzed the MBC of the clove essential oil and its major compound eugenol at concentrations of 10; 20; 30; 40; 50; 60; 70 and 80 mg.mL-1and also the quaternary ammonium at concentrations of 30; 40; 50; 60; 70; 80; 90 and 100 mg.mL-1 which were determined using the broth microdilution in 96-well polystyrene plates and incubated at 37 ° C for 48 hours. Throughout the experiment the antimicrobials were homogenized in BHI broth, added with 0.5% (v / v) Tween 80. For the adaptation of the planktonic cells, the sublethal concentration of 1/8 MBC of the antimicrobials was used, at 37 ° C, for 6 hours. To adapt the sessile cells, the sublethal concentration of 1/8 MBC of the antimicrobials of the planktonic cells was used at 37 ° C/48 h. For direct resistance induction of planktonic cells, that is, subjected to sublethal and then exposed to the same antimicrobial concentrations, there was no adaptation, the MBC remained the same. However, cross-adaptation of S. Enteritidis between clove essential oil and eugenol at pH was observed, and the microorganisms grew at pH 4.5 and 5.0, respectively. Cross-matching between the majoritarian component eugenol and the quaternary ammonium sanitizer was also observed. For the induction of direct and cross resistance of sessile cells, adaptation to eugenol was observed, with a minimum bactericidal concentrations of biofilm (MBCB) increased from 30 to 40 mg.mL-1, in both cases. It can be concluded that these antimicrobials can be used in the food industry, but preventive measures should be used so that the microorganism is not subjected to sublethal concentrations of these antimicrobials due to the acquisition of cross tolerance.